2019
DOI: 10.1073/pnas.1904210116
|View full text |Cite
|
Sign up to set email alerts
|

Inward-facing conformation of a multidrug resistance MATE family transporter

Abstract: Multidrug and toxic compound extrusion (MATE) transporters mediate excretion of xenobiotics and toxic metabolites, thereby conferring multidrug resistance in bacterial pathogens and cancer cells. Structural information on the alternate conformational states and knowledge of the detailed mechanism of MATE transport are of great importance for drug development. However, the structures of MATE transporters are only known in V-shaped outward-facing conformations. Here, we present the crystal structure of a MATE tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 78 publications
5
55
0
Order By: Relevance
“…Although controversial 25,35 , this conformation of TM1 was also captured in a crystal structure of a H + -coupled MATE from V. cholerae suggesting a conserved element of alternating access 23 Prominent discrepancies between predicted and experimental distributions are noted for the intracellular side of TM1, which in the IF structure unwinds leading to distance changes relative to TMs 3, 6, 11 and 12 (Figs. 5A, 6A).…”
Section: Protonation Induces Closing Of the Extracellular Sidementioning
confidence: 85%
See 2 more Smart Citations
“…Although controversial 25,35 , this conformation of TM1 was also captured in a crystal structure of a H + -coupled MATE from V. cholerae suggesting a conserved element of alternating access 23 Prominent discrepancies between predicted and experimental distributions are noted for the intracellular side of TM1, which in the IF structure unwinds leading to distance changes relative to TMs 3, 6, 11 and 12 (Figs. 5A, 6A).…”
Section: Protonation Induces Closing Of the Extracellular Sidementioning
confidence: 85%
“…In the OF MATE structures, the putative central substrate binding cavities are shielded from the cytoplasm by highly ordered and packed protein regions, suggesting that transition to an IF conformation requires extensive structural rearrangements. A view of these rearrangements was recently captured from an IF crystal structure of PfMATE 25 . This structure, determined in the presence of native P. furiosus lipids, showed a change in the orientation of the central cavity that exposes its lumen to the intracellular side.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1), critical elements of the transport mechanism remain unresolved. Substrate/ion antiport entails differential stability of the OF and IF conformations when either ligand is bound, yet Zakrzewska et al (25) found that the OF also crystallizes at low pH (pH 5 to 6.5), albeit in the absence of native lipids. This observation led the authors to question the role of protons in driving isomerization between OF and IF conformations.…”
Section: Significancementioning
confidence: 99%
“…In the OF MATE structures, the putative central substrate binding cavities are shielded from the cytoplasm by highly ordered and packed protein regions, suggesting that transition to an IF conformation requires extensive structural rearrangements. A view of these rearrangements was recently captured from an IF crystal structure of PfMATE (25). This structure, determined in the presence of native Pyrococcus furiosus lipids, showed a change in the orientation of the central cavity that exposes its lumen to the intracellular side.…”
mentioning
confidence: 99%